2008
DOI: 10.1097/nen.0b013e31818b4906
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Erythroid 2-Related Factor 2-Antioxidative Response Element Signaling Pathway in Motor Cortex and Spinal Cord in Amyotrophic Lateral Sclerosis

Abstract: Oxidative stress and inflammation are important pathogenetic mechanisms in amyotrophic lateral sclerosis (ALS). Nuclear erythroid 2-related factor 2 (Nrf2) is a basic region leucine-zipper transcription factor that binds to the antioxidant response element, thereby regulating the expression of many genes that are involved in cellular antioxidant and anti-inflammatory defense. Under normal conditions, Nrf2 activation is inhibited by Kelch-like ECH-associated protein 1 (Keap1). We investigated the potential invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(99 citation statements)
references
References 32 publications
3
94
1
1
Order By: Relevance
“…The KEAP1 RNA level was previously shown to be increased in the motor cortex but not the spinal cord of ALS patients compared to controls, although no significant differences were seen at the protein level (31). We detected increased KEAP1 protein levels in some but not all ALS patient lumbar spinal cord cytosolic fractions compared to controls, but this did not reach statistical significance (Fig.…”
Section: Rbm45/keap1 Interactions In Als Spinal Cordmentioning
confidence: 52%
See 2 more Smart Citations
“…The KEAP1 RNA level was previously shown to be increased in the motor cortex but not the spinal cord of ALS patients compared to controls, although no significant differences were seen at the protein level (31). We detected increased KEAP1 protein levels in some but not all ALS patient lumbar spinal cord cytosolic fractions compared to controls, but this did not reach statistical significance (Fig.…”
Section: Rbm45/keap1 Interactions In Als Spinal Cordmentioning
confidence: 52%
“…Whether oxidative stress is a primary event or merely a consequence of neurodegeneration in ALS is unclear; nevertheless, evidence for increased oxidative stress and ROS generation in both ALS patients and ALS transgenic models suggests that this pathway is a major contributory factor in motor neuron death (49,50). KEAP1 has been shown to localize to neuronal and cytoplasmic p62-positive inclusions in neurodegenerative diseases, including ALS (32), and altered levels of both NRF2 and KEAP1 as well as their downstream targets in ALS have also been described (27,31). In our current study, we demonstrate that a nuclear RNA binding protein, RBM45, can be translocated into the cytoplasm and modulate the KEAP1/NRF2 antioxidant response pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This extensive neuroinflammation and oxidative stress is consistent with elevated NF-κB activity concomitant with impaired Nrf2 activity [10,11], hence there is abundant evidence for inverse regulation of Nrf2 and NF-κB in neurodegenerative disease. Indeed, Nrf2 expression is diminished in human post-mortem tissue of AD and ALS patients [12,13]. Further evidence for the interplay between Nrf2 and NF-κB comes from experimental induction of inflammation.…”
Section: Inverse Regulation Of Nrf2 and Nf-κb In Neurodegenerationmentioning
confidence: 99%
“…Reduced expression of Nrf2 and selected downstream targets was seen at both the RNA and protein levels in the cellular model and NRF2 dysregulation was also demonstrated in isolated motor neurones from SOD1-related ALS cases. Subsequent work by Sarlette and colleagues has shown that NRF2 transcription and translation is also decreased in SALS cases (Sarlette et al 2008). Most recently, it has been demonstrated that activation of Nrf2 in NSC34 SOD1-related ALS cell models, primary motor neurone and astrocyte co-cultures and in the SOD1 G93A mouse model all improve neuronal survival (Neymotin et al 2011;Vargas et al 2008a).…”
Section: Results From Use Of Cellular Models Of Alsmentioning
confidence: 99%